Exploration of FPGA‐based electromagnetic transient real‐time simulation system design using high‐level synthesis. Issue 16 (7th January 2019) - Li, Qiao; Xiang, Yinxing; Mu, Qing; Zhang, Xing; Li, Xiongfei; He, Guanghui
Abstract : Field‐programmable gate array (FPGA)‐based simulation system is applied in real‐time electromagnetic transient (EMT) simulation for small time‐step simulation. However, the FPGA‐based simulation system requires handcrafted hardware description language (HDL) and significant design efforts. This paper explores FPGA‐based EMT real‐time simulation system design using high‐level synthesis (HLS) technology to accelerate the design process and improve the flexibility, because high‐level language can be transferred into HDL using HLS. Furthermore, loop unroll and pipeline optimisation directives are analysed and applied for HLS to improve the computation speed of the components. The system can simulate various components, including switches, R‐L‐C, voltage sources, current sources, and transmission lines. Especially, the system adopting double‐precision floating‐point calculation can support the network with 74 nodes and achieve 2 us for each small time step on Xilinx Virtex7‐690 T FPGA. Comparison of simulation results from offline simulation tools with those from the proposed simulation system validates the correctness of the FPGA‐based EMT simulation system using HLS technology.